PRIMARY ENEROPATHY-ASSOCIATED T-CELL EXTRNODAL LYMPHOMA DEBUTING WITH COMPLICATIONS. ANALYSIS OF TWO CASE REPORTS AND THE REASONS FOR THEIR UNFAVORABLE OUTCOME - A. Z. Almyashev; R. A. Ulyankina; P. I. Skopin; A. A. Ivashin; A. A. Mokhammed (Сибирский онкологический журнал)
Background. T-cell lymphoma with small and/or large bowel perforation is classified as a rare and extremely aggressive malignant non-Hodgkin’s lymphoma (NHL). There are two types of T-cell lymphomas:  enteropathyassociated T-cell lymphoma (EATL) and monomorphic epitheliotropic intestinal T-cell lymphoma (MEITL). The most common site of involvement is the small intestine.Case presentation. A 63-year-old woman and a 50-year-old woman presented with a rare form of primary peripheral T-cell extranodal enteropathy-associated lymphoma (EATL) positive for Cd20 and Cd30. postoperative histological and immunohistochemical examinations of the small intestine resection specimens revealed intestinal perforation.Conclusion. The delay in diagnosis, multiple lesions, complications, and the rapid disease progression ultimately led to the death of the patients.